MODERN TREATMENT OF CONGENITAL SYPHILIS (International journal of artificial intelligence, 2024)
Congenital syphilis is a clinical form of syphilis that occurs when a child is infected in utero with pale treponema. Congenital syphilis can manifest itself in various periods of a child's life, from prenatal to adolescent. It is characterized by specific syphilitic lesions of the skin, mucous membranes, bone tissue, somatic organs and nervous system. Diagnosis of congenital syphilis is based on the isolation of the pathogen from the blood, separated skin elements and cerebrospinal fluid; positive results of serological reactions and PCR diagnostics, examination of the state of internal organs. Treatment of congenital syphilis is carried out with antibiotics, bismuth preparations and non-specific means aimed at improving immunity.